Effects of Spaced Retrieval Training on Semantic Memory in Alzheimer's Disease: A Systematic Review. - Oren, Shiri; Willerton, Charlene; Small, Jeff (Journal of Speech, Language & Hearing Research, 2014)
Purpose: This article reports on a systematic review and meta-analysis of the effects of spaced retrieval training (SRT) on semantic memory in people with Alzheimer's disease (AD) or related disorder. Method: An initial systematic database search identified 454 potential studies. After screening and de-duplication, 35 studies that used SRT with the population of interest remained. The authors used an appraisal point system to evaluate the quality of the studies. Twelve of the 35 studies met inclusion and exclusion criteria and passed the appraisal point system cutoff. The 12 studies were classified as Level I and II evidence. Results: Although the 12 studies varied in terms of design, methodology, and quality, SRT was shown to have important positive effects on learning semantic information across the included studies. Conclusions: The findings indicate that SRT is an effective semantic memory training technique for people with AD, and consequently, recommendations are suggested for implementing SRT in practice settings. Continued research in this domain is also warranted to address limitations and gaps in the current body of research evidence, including variability in SRT protocols, effects of dementia severity on learning outcomes, maintenance effects, generalization, and the role of explicit and implicit learning in SRT.